Removal of sulfate and heavy metals by sulfate-reducing bacteria in an expanded granular sludge bed reactor - Liu, Zhuxiang (Environmental technology, 2018)
The objective of this study is to utilize an expanded granular sludge bed reactor for removing heavy metals and sulfate from synthetic acid-mine drainage (AMD) using sewage sludge fermentation centrate as the substrate. The reactor was bioaugmented with an enriched consortium of sulfate-reducing bacteria (SRB). The bioreactor performance was studied with different chemical oxygen demand [Formula: see text] ratios, liquid upflow velocity (Vup), hydraulic retention time (HRT) and influent pH. The highest COD, sulfate and heavy metal removal efficiencies were achieved at a [Formula: see text] ratio of 1.5, Vup of 4.0 m/h, HRT of 15 h and influent pH of 6.0 (68.2%, 92.1% and 100%, respectively). The activity of SRB greatly increases the effluent pH. Even at an influent pH of 3.0, 60.8% of sulfate, 41.3% of COD and 91.2% of heavy metals could be removed, and the effluent quality can meet the national discharge standard of China. The activity tests demonstrate that the sludge fermentation centrate is an excellent carbon source for SRB. This study shows the potential of synchronous treatment of residual sewage sludge and treatment of AMD